Programming your home automate with Arduino, Android, and your computer - Riley, Mike (Pragmatic Bookshelf, 2012)
In Programming Your Home, technology enthusiast Mike Riley walks you through a variety of custom home automation projects, ranging from a phone application that alerts you to package deliveries at your front door to an electronic guard dog that will prevent unwanted visitors.--
Includes bibliographical references (page 211) and index
Keywords: Android (Electronic resource); Home automation -- Amateurs' manuals; Arduino (Programmable controller); G1 (Smartphone); Domotique; Manuels d'amateurs; Arduino (Automate programmable); G1 (Téléphones intelligents); Home automation; Handbooks and manuals